2016
DOI: 10.1123/jsep.2016-0256
|View full text |Cite
|
Sign up to set email alerts
|

Should We Be Looking at the Forest or the Trees? Overall Psychological Need Satisfaction and Individual Needs as Predictors of Physical Activity

Abstract: The objectives of this study were twofold: (a) examine if measures designed to assess satisfaction of competence, autonomy, and relatedness needs in the physical activity domain can represent both general and specific needs satisfaction, and (b) assess if the specific needs are associated with concurrent moderate-to-vigorous intensity physical activity (MVPA) participation (Time 1) and MVPA participation 4 months later (Time 2), beyond general psychological needs satisfaction (PNS). Data from 544 adolescents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 60 publications
(103 reference statements)
6
23
0
2
Order By: Relevance
“…Satisfaction of basic psychological needs and self-determined motivation are associated with enjoyment and effort in performing activities and other positives outcomes (Deci and Ryan, 2017). For instance, Brunet et al (2016) observed in adolescents that autonomy, competence and relatedness predicted moderate-to-vigorous-intensity physical activity 4 months later. Similarly, Richards et al (2017) observed that self-determined motivation predicted physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction of basic psychological needs and self-determined motivation are associated with enjoyment and effort in performing activities and other positives outcomes (Deci and Ryan, 2017). For instance, Brunet et al (2016) observed in adolescents that autonomy, competence and relatedness predicted moderate-to-vigorous-intensity physical activity 4 months later. Similarly, Richards et al (2017) observed that self-determined motivation predicted physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…This new examination has revealed ratings of need satisfaction to simultaneously reflect respondents’ global levels of need satisfaction across all three needs as well as the more specific satisfaction of their needs for relatedness, competence, and autonomy left unexplained by this global level. This conclusion appears to hold in the educational (Garn, Morin, & Lonsdale, ; Gillet et al, ), general life (Tóth‐Király, Morin, Bőthe, Orosz, & Rigó, ), sport (Brunet, Gunnell, Teixeira, Sabiston, & Bélanger, ), and work (Bidee, Vantilborgh, Pepermans, Griep, & Hofmans, ; Sánchez‐Oliva et al, ) domains. In practical terms, these studies show that it is possible to simultaneously obtain a direct estimate of participants’ global need satisfaction levels encompassing all three needs, together with a non‐redundant estimate of the unique satisfaction of each specific need over and above that global level (i.e., expressed as deviations from that global level, and thus providing a direct estimate of imbalance in the extent to which each need is satisfied relative to the other needs for a specific individual).…”
Section: The Critical Role Of Need Satisfactionmentioning
confidence: 95%
“…In this regard, an individual fulfilling their basic psychological needs (autonomy, competence, and relationship) will see their satisfaction with and commitment to ongoing activities increase [7], for example, their levels of physical activity during leisure time [18], which in turn translate into an improvement in their academic performance [19,20]. It is worth underscoring how important it is that students feel satisfied with PE class so that their levels of physical activity during their leisure time increase [21].…”
Section: Introductionmentioning
confidence: 99%